Afterslip Moment Scaling and Variability From a Global Compilation of Estimates. Issue 4 (12th April 2022) - Churchill, R. M.; Werner, M. J.; Biggs, J.; Fagereng, Å.
Abstract: Aseismic afterslip is postseismic fault sliding that may significantly redistribute crustal stresses and drive aftershock sequences. Afterslip is typically modeled through geodetic observations of surface deformation on a case‐by‐case basis, thus questions of how and why the afterslip moment varies between earthquakes remain largely unaddressed. We compile 148 afterslip studies following 53 M w 6.0–9.1 earthquakes, and formally analyze a subset of 88 well‐constrained kinematic models. Afterslip and coseismic moments scale near‐linearly, with a median Spearman's rank correlation coefficient (CC) of 0.91 after bootstrapping (95% range: 0.89–0.93). We infer that afterslip area and average slip scale with coseismic moment as M o 2 / 3 M_o^2/3 and M o 1 / 3 M_o^1/3, respectively. The ratio of afterslip to coseismic moment ( M rel ) varies from <1% to >300% (interquartile range: 9%–32%). M rel weakly correlates with M o (CC: −0.21, attributed to a publication bias), rupture aspect ratio (CC: −0.31), and fault slip rate (CC: 0.26, treated as a proxy for fault maturity), indicating that these factors affect afterslip. M rel does not correlate with mainshock dip, rake, or depth. Given the power‐law decay of afterslip, we expected studies that started earlier and spanned longer timescales to capture more afterslip, but M rel does not correlate with observation start time or duration. Because M rel estimates for a single earthquake can vary by an order of magnitude, we propose that modeling uncertainty currently presents a challenge for systematic afterslip analysis. Standardizing modeling practices may improve model comparability, and eventually allow for predictive afterslip models that account for mainshock and fault zone factors to be incorporated into aftershock hazard models. Plain Language Summary: Afterslip is the gentle slipping, or sliding, of a fault over several months or years following an earthquake. Afterslip is not an earthquake but does release energy that may trigger other earthquakes, called aftershocks. Therefore, we wish to understand why some earthquakes produce much more afterslip than others. We compile and analyze 148 afterslip studies (following 53 earthquakes) from the literature and show that the amount of afterslip is mainly determined by the magnitude of the earthquake. However, there is considerable variation beyond this dependence which might be linked to characteristics of the earthquake and fault setting. We find that more afterslip tends to occur when the earthquake rupture is less elongated in shape, or when the causative fault has a greater long‐term slip rate. However, different studies following the same earthquake sometimes yielded different moment estimates that we cannot explain. We propose that the unknowns and methodological differences in afterslip modeling currently make comparing events difficult; future methods should be more standardized so that afterslip can be meaningfully considered in hazard models following an earthquake. Key Points: We compile 148 afterslip studies after 53 earthquakes to probe the scaling and variability of aseismic afterslip moment Afterslip moment scales near‐linearly with the coseismic moment but varies from <1% to >300% of coseismic moment between earthquakes Different modeling approaches appear to be the dominant cause of variability, but fault slip rate and rupture shape may exert some control